Designing Innovative Packaging to Enhance the Appeal of Adifidz Putra's Small and Medium Enterprises Products - habibie, indra; Akbar, Rahmad; Nurkholis, Nurkholis; Yetti, Dzulhijjah; Am, Andri Nofiar; Febrianton, Adi; Kurniaty, Tri (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2024)
The rapid development of the global market is in the global industry where companies must have the ability to compete globally in the face of advancing times. Therefore, this global market development becomes a challenge for companies, including the Adifidz Putra beef skin cracker Small and Medium Enterprises (SMEs) in Bangkinang City, which must be able to compete by offering their consumers the best taste, quality, service, price, and packaging design compared to other competing products, so that they can continue to maintain their performance. Therefore, it is necessary to develop the packaging design for the skin cracker products from SMEs Adifidz Putra in Bangkinang City by applying the Kansei Engineering approach. This approach takes into account the emotional and psychological aspects of product packaging with the aim of creating a positive experience for consumers. The Kansei Engineering method will be used to link the physical characteristics of the packaging with the emotional responses expected from consumers. It is hoped that the results of this research will enhance product appeal and consumer satisfaction, while helping SMEs Adifidz Putra to improve their marketing efforts and increase the competitiveness of their products.